Urban Solid Waste Management Crisis: An Assessment Of The Enabling Environment For Private Sector Participation In La Nkwantanang-Madina Municipality. - Sarpong, J. (University of Ghana, 2022)
Environmental concerns have gotten a lot more attention as a result of the growing focus on sustainable development. Waste management, especially sustainable waste management (SWM) appears to be an environmental issue that has gained both study and policy attention. The goal of this study is to assess the enabling environment for private sector participation in the management of solid waste in the La Nkwantanang-Madina Municipality. The La Nkwantanang-Madina Municipal Assembly, private waste management businesses, and residents of La Nkwantanang-Madina Municipality make up the study's population. The Municipality was divided into three socioeconomic classes (high, middle, and low–income residential sectors) based on wealth, population density, housing quality, and various economic criteria. Given the character of the respondents for this study, two (2) key data collection instruments were used: a questionnaire and an interview guide. A total of one hundred and eighty-six (186) sample size was obtained for the households out of 204, representing a response rate of 91%. Purposive sampling was also used to obtain data from specific groups based on their roles in solid waste management in the study area. These included the Municipal Environmental Health Officer, Municipal Planning Officer, Assembly members, and Private Waste Contractors such as Bright Waste Company Limited. The study's findings suggested that there are clear-cut arrangements for handling solid waste in the municipality but there are deficits in the application of these arrangements in the management. The findings also revealed that the solid waste management system in the La-Nkwantanang Madina Municipality is that of collection and disposal. The municipality is currently not treating or recycling waste as far as the management of waste is concerned. The study concludes by recommending that local government entities' technical and financial capacities must be enhanced to help regulate and enforce sanitation laws and bye-laws. It is also very necessary for the government to increase investment in final disposal sites and transfer stations.
MPhil. In Geography And Resource Development
Keywords: Urban; Waste Management; Environment; Municipality; Sector